Elevated TREM2 Gene Dosage Reprograms Microglia Responsivity and Ameliorates Pathological Phenotypes in Alzheimer's Disease Models - Lee, C Y Daniel; Daggett, Anthony; Gu, Xiaofeng; Jiang, Lu-Lin; Langfelder, Peter; Li, Xiaoguang; Wang, Nan; Zhao, Yingjun; Park, Chang Sin; Cooper, Yonatan; Ferando, Isabella; Mody, Istvan; et al. (Neuron (Cambridge, Mass.), 2018)
Variants of TREM2 are associated with Alzheimer's disease (AD). To study whether increasing TREM2 gene dosage could modify the disease pathogenesis, we developed BAC transgenic mice expressing human TREM2 (BAC-TREM2) in microglia. We found that elevated TREM2 expression reduced amyloid burden in the 5xFAD mouse model. Transcriptomic profiling demonstrated that increasing TREM2 levels conferred a rescuing effect, which includes dampening the expression of multiple disease-associated microglial genes and augmenting downregulated neuronal genes. Interestingly, 5xFAD/BAC-TREM2 mice showed further upregulation of several reactive microglial genes linked to phagocytosis and negative regulation of immune cell activation. Moreover, these mice showed enhanced process ramification and phagocytic marker expression in plaque-associated microglia and reduced neuritic dystrophy. Finally, elevated TREM2 gene dosage led to improved memory performance in AD models. In summary, our study shows that a genomic transgene-driven increase in TREM2 expression reprograms microglia responsivity and ameliorates neuropathological and behavioral deficits in AD mouse models.